Biological and social reasons of child mortality in the Danzing District in the second part of the 19th century - Liczbińska, Grażyna (Polskie Towarzystwo Antropologiczne, 1999)
The purpose of this work is to characterise the child mortality in urban and rural areas of the Danzing (Gdańsk) District and in the city of Danzing, in the second half of the 19th century. The study material encompassed the demographic data on mortality coming from the 19th century Prussian statistical yearbooks. The basic mortality measures such as infant death rates, neonatal and postneonatal death rates and child death rates were computed for selected years of the second half of the 19th century. Life tables were constructed in accordance with Halley's method and based on the assumption the population was of stationary type. Further, the causes of child deaths and the occupational structure of the families of deceased children were discussed.